2015
DOI: 10.1111/gcbb.12245
|View full text |Cite
|
Sign up to set email alerts
|

A global meta‐analysis of forest bioenergy greenhouse gas emission accounting studies

Abstract: The potential greenhouse gas benefits of displacing fossil energy with biofuels are driving policy development in the absence of complete information. The potential carbon neutrality of forest biomass is a source of considerable scientific debate because of the complexity of dynamic forest ecosystems, varied feedstock types, and multiple energy production pathways. The lack of scientific consensus leaves decision makers struggling with contradicting technical advice. Analyzing previously published studies, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 52 publications
1
61
0
3
Order By: Relevance
“…To date, studies have mostly focused on estimating a unique and precise C debt repayment time or C parity time for particular case studies without addressing any sources of variation. For correct accounting, however, estimates need to take uncertainty into account, from variations in the biomass supply chain to the realism of the counterfactual scenario (Johnson et al ., ; Bowyer et al ., ; Buchholz et al ., , ). We found that the length of the uncertainty period can be short and inconsequential for some scenarios (e.g., harvest residues).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies have mostly focused on estimating a unique and precise C debt repayment time or C parity time for particular case studies without addressing any sources of variation. For correct accounting, however, estimates need to take uncertainty into account, from variations in the biomass supply chain to the realism of the counterfactual scenario (Johnson et al ., ; Bowyer et al ., ; Buchholz et al ., , ). We found that the length of the uncertainty period can be short and inconsequential for some scenarios (e.g., harvest residues).…”
Section: Discussionmentioning
confidence: 99%
“…Factors regulating the GHG mitigation potential of bioenergy projects and the underlying large variation in C parity times include biomass feedstock source and processing, the type of fossil fuel replaced, energy conversion efficiency, tree growth rate, and the definition of the counterfactual ‘reference’ scenario, that is, what would have happened to the forest land if biomass had not been sourced and used for bioenergy? (Lamers et al ., ; Buchholz et al ., , ). Because many of those factors usually differ among studies, it is often difficult to compare C parity times among a variety of forest bioenergy uses.…”
Section: Introductionmentioning
confidence: 99%
“…A critical consideration with most of these studies is that in their calculations of the life‐cycle GHG emissions from bioenergy systems they consider combustion of biogenic fuels to be carbon neutral provided there is no loss of carbon stock in the forest. Some stakeholders have raised concerns with this approach . However, as this is the current approach of the EC, we do not consider GHG balance to be a practical constraint on biomass sourcing from the US SE for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Risks and consequences of storms, wildfires, forest pests and diseases are also not considered in this study, although we acknowledge that such events can have a strong influence on net carbon balances (cf. Buchholz et al ., ).…”
Section: Introductionmentioning
confidence: 97%